Higher order stochastic averaging method for mechanical systems having two degrees of freedom - Tinh, Nguyen Duc (Vietnam Journal of Mechanics, 2004)
Higher order stochastic averaging method is widely used for investigating single-degree-of-freedom nonlinear systems subjected to white and coloured random noises.In this paper the method is further developed for two-degree-of-freedom systems. An application to a system with cubic damping is considered and the second approximation solution to the Fokker-Planck (FP) equation is obtained